ARTEMISIA SIEVERSIANA WILLD. IN TRANSBAIKALIA: FEATURES OF CENOFLORA AND INTRASPECIFIC VARIABILITY - A. B. Sakhyaeva; B. B. Namzalov (Труды по прикладной ботанике, генетике и селекции)
Background. Artemisia sieversiana Willd. is a Eurasian species of the genus Artemisia L., belonging to the group of monocarpic  annual/biennial plants. This species is not only a weed, but also one  of the valuable medicinal plants of folk and Tibetan medicine.  However, the data about the species' biology and ecology are very  scanty. The study of cenoflora with the occurrence of A. sieversiana is one of the main tasks for the understanding of the species.Results. In the Transbaikalian vegetation, A. sieversiana is  represented by three morphotypes: (1) the forest-steppe  morphotype, when individual plants are short (up to 20-25 cm) and  characterized by a very compressed paniculate inflorescence, large  baskets sitting one by one on very short stalks or peduncles; (2) the  adventive one, characterized by large sizes, the stem in the upper  half ramified into a large paniculate inflorescence, and the plant  height reaching up to 100 cm; and (3) the fallow one, with plants of  average height (20-40 cm), when the panicle is well developed, but  systems of secondary flower-bearing shoots in the sinuses of the  upper leaves are relatively poorly formed. In the flora of communities where A. sieversiana is present, 146 species of  higher vascular plants belonging to 42 families and 74 genera were  identified. Asteraceae (24%), Poaceae (11%), Fabaceae (7%),  Rosaceae (7%), Brassicaceae (6%) occupy the leading position in  the spectrum of multispecies families. Among the life forms,  perennial herbaceous plants (48%) prevail as well as annual/biennial herbaceous monocarpicles (28%). Species belonging to the taproot (34.2%), long rhizome (15.06%), racemose root  (9.5%) and root sucker (7.5%) groups are widely represented as a  result of adaptation to abrupt temperature fluctuations and lack of  moisture. Ecological analysis showed that xerophytes (25%),  mesoxerophytes (22%) and xeromesophytes (21%) occupy the  prevailing positions, which attests to the extreme continental climate in the region. Species of the mesophyte group (15%) are  represented by medium-scale percentage; these are mostly the  plants of more moderately moist soils. According to the ratio of geographic elements, meadow-steppe and steppe Eurasian  (23%), polyzonal (weedy), and Holarctic (20%) species dominate in  the cenoflora of A. sieversiana communities, with Central Asian  desert-steppe species (14%) also present. Conclusion. The analysis shows the special features of the vegetation of plant communities with A. sieversiana. Species of the  meadow-steppe geographic group with a wide range of distribution  are typical for them. Predominance of taproot mono- and  polycarpicles of xerophytic ecology was observed. In Transbaikalia,  A. sieversiana is differentiated into three morphotypes. With this, the forest-steppe type, if compared with the adventive and fallow forms, is distinguished by a set of morphological traits in its vegetative and  generative spheres, which may lead to its recognition as a separate botanical variety.